Mobilizing gay Singapore : rights and resistance in an authoritarian state - Chua, Lynette J., 1977- (Sexuality studies., 2014)
For decades, Singapore's gay activists have sought equality and justice in a state where law is used to stifle basic civil and political liberties. In her groundbreaking book, Mobilizing Gay Singapore, Lynette Chua asks, what does a social movement look like in an authoritarian state? She takes an expansive view of the gay movement to examine its emergence, development, strategies, and tactics, as well as the roles of law and rights in social processes. Chua tells this important story using in-depth interviews with gay activists, observations of the movement's ac.